Penerapan Analytical Hierarchy Process (Ahp) Pada Sistem Pendukung Keputusan Untuk Menentukan Kualitas Kayu (Studi Kasus di Dinas Pertanian, Perkebunan Dan Kehutanan Kota Sungai Penuh) - SRI MURTIA; FERDINAL R (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
ABSTRACT Has developed a new system that is implemented in a decision support system. This system is used tohelp facilitate the processing of data in determine the quality of wood. The entire data collection relating to the quality of wood. includes data aged wood, the data wood texture, complexion data. Wooden ciolence data, place to grow timber data. The method used for data processing using AHP (Analytic Hierarchy Process). Stages in AHP begins theprocess of defining the problem, the manufacture of structural hierarchy that begins with a generalpurpose, followed by the criteria and alternatives choices, Making pairwise comparison matrix, normalize the data, Calculating eigenvalues vector and tested for consistency, Calculating eigen vector of each pairwise comparison matrix, Test consistency hierarchy. If it does not comply with CR <0.100 then the assessment should be repeated again. The results showed that application of decision support systems are used to determine the quality of the wood it can perform calculations with AHP (AnalyticHierarchy Process) is faster than manual calculation so that the bias is more efficient and the accuracy of the data is already close to perfect. Keywodrs : Decision Support System, AHP, The Quality Of Wood.